EXPLORING TAX AVOIDANCE MECHANISMS : FINANCIAL FACTORS AND FIRM VALUE IN INDONESIA'S FINANCIAL SECTOR - Putri, Vidiyanna Rizal; Zakaria, Nor Balkish; Nelmida; Tidespania Tubarat, Chara Pratami; Mohamed Izwan, Iylia Dayana (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
The relationship between financial factors and tax avoidance has become an increasingly important topic in corporate finance and taxation. This study examines the impact of financial derivatives, debt shifting, and transfer pricing on tax avoidance, with firm value as a moderating variable. The research focuses on conventional banks and non-bank financial institutions listed on the Indonesia Stock Exchange from 2019 to 2023. Using a purposive sampling method, 69 companies were selected, excluding Islamic banks, regional development banks, and Islamic financial institutions. The sample includes only firms that did not experience losses during the research period, as tax obligations do not apply to loss-making businesses.Employing EViews 9 for data analysis, the findings indicate that debt shifting negatively affects tax avoidance, while financial derivatives show no significant effect. In contrast, transfer pricing positively influences tax avoidance. However, firm value does not significantly moderate the relationships between tax avoidance and debt shifting or financial derivatives. Firm value, however, does moderate the relationship between transfer pricing and tax avoidance. Among the control variables, debt shifting negatively affects tax avoidance, maturity positively influences tax avoidance, and company growth has no significant effect. These findings provide insights into the financial strategies affecting tax avoidance in Indonesia’s financial sector, contributing to the broader discussion on corporate tax planning and regulatory implications.